Engineers and the law : an overview - Schoumacher, Bruce (New York : Van Nostrand Reinhold Company, 1986)
This book is primarily a survey of specific legal topics with which an engineer may have be familiar in order to practice.
Part I. Foundations of the law -- Part II. Legal responsibilities of the engineer -- Part III. Contracts -- Part IV. Other areas of the law.
Includes index.
Keywords: ENGINEERS -- LEGAL STATUS, LAWS, ETC -- UNITED STATES